ЅTRАTЕGІ АMЕRІKА ЅЕRІKАT MЕMBЕNDUNG DОMІNАЅІ TІОNGKОK DІ АЅІА MЕLАLUІ ІNDО-PАЅІFІK - Agung Yudhistira Nugroho; Wіntа Br Pаndіа (GLOBAL INSIGHT JOURNAL, 2021)
ABSTRACT            The statement of nUnited States President Donald Trump "You Say Asia-Pacific, I Say Indo-Pacific" suggests for changes in the geopolitical concentration of the United States in Asia to increase influence in the region. The progressive steps taken by America are contained in the concept of "free open Indo-Pacific" which involves several countries in Asia as the US grand strategy. The presence of the United States alliance or the designation in the Indo-Pacific, namely The Quad emphasized the seriousness of the United States in working on the Indo-Pacific concept. The Indo-Pacific which is promoted by the United States aims to stem the influence of China domination after the United States' exit in the Trans Pacific Partnership (TPP) cooperation forum. America needs a new 'container' to be able to increase its influence in the Asian region and the Indo-Pacific concept is the answer. The Indo-Pacific United States which promotes cooperation and investment is prepared as the main strategy using the concepts of geopolitics and geoeconomics. The United States in the Indo-Pacific again reaffirmed the existence of hegemonic power coupled with moving the quad as an additional strength of the United States in the region. Opportunities and challenges will be faced by the United States in implementing this strategy, as well as countries that are members of the quad, it cannot be denied that the interests to be achieved in the future will be different. In addition to the anarchic international system, there is the term that there is no "eternal friend", but eternal importance. Keywords: Indo-Pacific, Strategy, United States, Hegemony, Investment, Cooperation AbstrakPernyataan Presiden Amerika Serikat Donald Trump “You Say Asia-Pasifik, I Say Indo-Pacific” mengisyaratkan bagi perubahan konsentrasi geopolitik Amerika Serikat di Asia untuk meningkatkan pengaruh di kawasan. Langkah progesif yang ditempuh Amerika tertuang dalam konsep “free open Indo-Pacific” yang melibatkan beberapa negara di Asia sebagai grand strategy AS. Hadirnya negara aliansi Amerika Serikat atau sebutan dalam Indo-Pasifik, yaitu The Quad menegaskan keseriusan Amerika Serikat dalam menggarap konsep Indo-Pasifik. Indo-Pasifik yang diusung oleh Amerika Serikat bertujuan untuk membendung pengaruh dominasi Tiongkok setelah keluarnya Amerika Serikat dalam forum kerja sama Trans Pacific Partnership (TPP). Amerika membutuhkan ‘wadah’ baru untuk dapat kembali meningkatkan pengaruhnya di kawasan Asia dan konsep Indo-Pasifik adalah jawabannya. Indo-Pasifik Amerika Serikat yang mengedepankan kerja sama dan investasi disusun sebagai strategi utama dengan menggunakan konsep geopolitik dan geoekonomi. Amerika Serikat dalam Indo-Pasifik kembali  menegaskan eksistensi sebagai kekuatan hegemon dibarengi dengan menggerakkan the quad sebagai kekuatan tambahan Amerika Serikat di kawasan. Peluang dan tantangan akan banyak dihadapi oleh Amerika Serikat dalam melaksanakan strategi tersebut, seperti halnya negara-negara yang tergabung dalam the quad, tidak dapat dibantah bahwasanya kepentingan yang ingin dicapai kedepannya akan berbeda. Di tambah dalam sistem internasional yang anarki ada istilah tidak ada “teman abadi”, melainkan kepentingan selamanya yang abadi. Kata Kunci: Indo-Pasifik, Strategi, Amerika Serikat, Hegemoni, Investasi, Kerja sama